Exposures and reported symptoms associated with occupational deployment to the Buncefield fuel depot fire, England 2005. Issue 6 (19th October 2007) - Morgan, O; Verlander, N Q; Kennedy, F; Moore, M; Birch, S; Kearney, J; Lewthwaite, P; Lewis, R; O'Brian, S; Osman, J; Reacher, M
Abstract : Objectives: An explosion at the Buncefield fuel depot outside London occurred on 11 December 2005. We conducted a retrospective cohort study of airborne exposures and health status for workers deployed. Methods: Deployed individuals were identified through their occupational health departments. We sent a self-completion questionnaire asking about health symptoms during the burn and post-burn phases. The prevalence of health symptoms in workers was compared to symptoms in local residents not under the smoke plume. Results: Of 1949 eligible individuals, 815 returned questionnaires (response rate 44). Respiratory protection was used by 39. Symptoms were reported by 41 of individuals during the burn phase compared with 26 in the post-burn phase. In a final multivariable model, reporting of any symptoms was associated with deployment inside the inner fire cordon during the burn phase (OR 2.07, 95 CI 1.24 to 3.47) and wearing a face mask (OR 2.33, 95 CI 1.67 to 3.26). Compared with the general public, eye irritation (prevalence ratio (PR) 2.1, 95 CI 1.5 to 3.0), coughing (PR 1.3, 95 CI 1.0 to 1.8) and headaches (PR 1.7, 95 CI 1.2 to 2.5) were more common in workers deployed during the burn phase but not the post-burn phase. Conclusions: Increased reporting of symptoms close to the fire during the burn phase was consistent with increased exposure to products of combustion, although no major acute illness was reported. That only a minority of individuals used face masks, which were not protective for symptoms, raises questions about the availability of adequate respiratory protection for such incidents.